Associations Between Type and Route of Hormone Use on Urinary Incontinence and Pelvic Organ Prolapse in Premenopausal and Postmenopausal Women. Issue 2 (March 2018) - Cardenas-Trowers, Olivia Orlinda; Borgstrom, Mark; Addis, Ilana
Abstract : Objective: The aim of this study was to evaluate the associations between type and route of hormone use and urinary incontinence (UI) and pelvic organ prolapse (POP) in premenopausal and postmenopausal women. Methods: The authors used the National Health and Nutritional Examination Survey database for data from 2005–2006, 2007–2008, 2009–2010, and 2011–2012. Seven thousand sixty-six of the women included were premenopausal, and 5387 were postmenopausal. Premenopausal women were younger than 51 years and reported menstrual periods in the last 12 months. Postmenopausal women reported being in natural or surgical menopause. Urinary incontinence was defined as experiencing urinary leakage "less than once a month" or more. Pelvic organ prolapse was defined as an affirmative response to "experience bulging in the vaginal area." Hormone route and use were stratified in years. Pearson χ 2 and Pearson correlations were used, with P < 0.05 considered significant. Results: In premenopausal women, birth control pills, estrogen/progestin pills, and estrogen-only patch use are associated with UI ( P < 0.05). Birth control pills are associated with both UI and POP in premenopausal women ( P < 0.05 for UI and POP). In postmenopausal women, estrogen-only pills, and estrogen/progestin pill use are associated with UI ( P < 0.05). Birth control pill use is associated with POP in postmenopausal women ( P = 0.029). Neither estrogen patch nor estrogen/progestin patch is associated with UI or POP in postmenopausal women. Conclusions: Type and route of hormone use have varied associations with UI and POP in premenopausal and postmenopausal women. Prospective studies are needed to further evaluate the effect of hormone type and route on UI and POP in premenopausal and postmenopausal women. Abstract : Type and route of hormone use have varied associations with urinary incontinence and pelvic organ prolapse in premenopausal and postmenopausal women.